Ribosome Profiling Reveals Pervasive Translation Outside of Annotated Protein-Coding Genes - Nicholas T. Ingolia; Gloria A. Brar; Noam Stern-Ginossar; Michael S. Harris; Gaëlle J.S. Talhouarne; Sarah E. Jackson; Mark R. Wills; Jonathan S. Weissman (Cell Reports, 2014)
Ribosome profiling suggests that ribosomes occupy many regions of the transcriptome thought to be noncoding, including 5′ UTRs and long noncoding RNAs (lncRNAs). Apparent ribosome footprints outside of protein-coding regions raise the possibility of artifacts unrelated to translation, particularly when they occupy multiple, overlapping open reading frames (ORFs). Here, we show hallmarks of translation in these footprints: copurification with the large ribosomal subunit, response to drugs targeting elongation, trinucleotide periodicity, and initiation at early AUGs. We develop a metric for distinguishing between 80S footprints and nonribosomal sources using footprint size distributions, which validates the vast majority of footprints outside of coding regions. We present evidence for polypeptide production beyond annotated genes, including the induction of immune responses following human cytomegalovirus (HCMV) infection. Translation is pervasive on cytosolic transcripts outside of conserved reading frames, and direct detection of this expanded universe of translated products enables efforts at understanding how cells manage and exploit its consequences.